PSYCHIATRIC DISORDERS IN CHILDREN: PATTERN AND CORRELATES AMONG THOSE REPORTING TO A TERTIARY CARE HOSPITAL - Amin, Malik Awais; Kamran, Muhammad; Rauf, Shehzad; Bukhsh, Sumaira; Gul, Isbah; Tabassum, Ahmed Shoaib (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the pattern of psychiatric disorders among children reporting to the Psychiatry department Pakistan Naval Ship Shifa Hospital, Karachi. Study Design: Comparative cross sectional study. Place and Duration of Study: Psychiatry department Pakistan Naval Ship Shifa Hospital, Karachi, from Feb to Aug 2018. Methodolgy: A total of 100 children, aged between 6-12 years of age, both male and female, meeting the selection criteria of the study, presenting to the Psychiatry department at Pakistan Naval Ship Shifa Hospital, were enrolled for this study. Informed consent was taken from the parents. The consultant psychiatrist interviewed the patients and diagnosed any psychiatric disorders based on international classification of diseases version 10. The data was recorded on the study proforma. Results: Out of a total of 100 children, 66 (66%) were male, while 34 (34%) were female. The mean age of the participating children was 8.66 + 1.97 years. The most common psychiatric disorder was attention deficit hyperactivity disorder 44 (44%), followed by depression 30 (30%). Other diagnoses included oppositional defiant disorder 12 (12%), conduct disorder 9 (9%) and separation anxiety disorder 5 (5%). Conclusion: Attention deficit hyperactivity disorder and depression are amongst the quite prevalent psychiatric disorders, than that was considered earlier.